The construction of enzymolyzed α-lactalbumin based micellar nanoassemblies for encapsulating various kinds of hydrophobic bioactive compounds. Issue 12 (13th November 2019) - Hu, Yulin; Bao, Cheng; Li, Dan; You, Lingxin; Du, Yizheng; Liu, Bin; Li, Xin; Ren, Fazheng; Li, Yuan
Abstract : Protein-based nanoassemblies can encapsulate hydrophobic compounds into their hydrophobic region and effectively improve their aqueous solubility and stability. Abstract : Protein-based nanoassemblies can encapsulate hydrophobic compounds into their hydrophobic region and effectively improve their aqueous solubility and stability. However, hydrolyzed food protein based micellar nanoassemblies and their interaction with different hydrophobic compounds are less understood. Here, 20 nm α-lactalbumin (α-lac) micellar nanoassemblies were constructed via self-assembly of partially hydrolyzed α-lac peptides by Bacillus licheniformis proteinase. We identified three fractions of peptides which reorganized into this kind of nanomicelle after exposure of α-lac hydrophobic groups. Moreover, four hydrophobic compounds (curcumin, quercetin, astaxanthin, coenzyme Q10) were successfully loaded into nanomicelles mainly via hydrophobic interactions. Among these four compounds, curcumin was most encapsulated in micelles due to its smaller molecular weight, high hydrophobicity and less steric hindrance. The strongest interaction was also observed between curcumin and nanomicelles. Finally, their aqueous solubility and UV stability after micellar encapsulation were significantly improved. This demonstrated that α-lac micelles are promising delivery systems for hydrophobic compounds.